Effect of some specialized exercises to improve balance during the performance of theRotation on one handle on the pommel horse for men - Sakran Hamza, Amer (Journal of Physical Education, 2012)
The study aimed to develop a set ofspecialized exercises assistance and developed by the researcher to develop the skill of turning on one handle and on a pommel horse andthe importance of developing this skill is shows through being one of the skills and difficult task, which is the basis for many of the skills a high difficulty on the pommel horse.Sample were (3 players) junior ages (13-15) years were selected, The researcher used the experimental method with a single way pre and posttest for the purpose of testing his hypothesis, And concluded that there is significanteffect of specialized exercises that help developand put in the number of spins on one handle as well as increased balance and support, the researcher recommended the adoption ofthe exercises contained in the research as a basis for the training of young players.